Polymerization of rac‐Lactide Using Achiral Iron Complexes: Access to Thermally Stable Stereocomplexes. Issue 36 (12th April 2019) - Marin, Paul; Tschan, Mathieu J.‐L.; Isnard, Florence; Robert, Carine; Haquette, Pierre; Trivelli, Xavier; Chamoreau, Lise‐Marie; Guérineau, Vincent; del Rosal, Iker; Maron, Laurent; Venditto, Vincenzo; Thomas, Christophe M.
Abstract: Enantiopure poly(lactic acid) (PLA) can form stereocomplexes when enantiomeric PLA chains are mixed in equivalent amounts. Such materials provide interesting features that might be suitable for numerous applications. Despite several advantages, the main drawback of PLA is its narrow window of processing, thus limiting its use for industrial applications. Reported herein are achiral iron complexes, that are highly active, productive, and stereoselective under mild reaction conditions for the ring‐opening polymerization of lactide. The corresponding catalytic systems enable the production of stereoblock polymers with high molecular weights, allowing the formation of thermally stable and industrially relevant stereocomplexes. Abstract : Chainlinks : Enantiopure poly(lactic acid) (PLA) forms stereocomplexes when enantiomeric PLA chains are mixed in equivalent amounts. The reported achiral iron complexes are highly active, productive, and stereoselective under mild reaction conditions for the ring‐opening polymerization of lactide. The corresponding catalytic systems enable the production of stereoblock polymers with high molecular weights.